Circulating Microvesicles Are Elevated Acutely following Major Burns Injury and Associated with Clinical Severity - O’Dea, Kieran P. (PLoS One, 2016)
Microvesicles are cell-derived signaling particles emerging as important mediators and biomarkers of systemic inflammation, but their production in severe burn injury patients has not been described. In this pilot investigation, we measured circulating microvesicle levels following severe burns, with severe sepsis patients as a comparator group. We hypothesized that levels of circulating vascular cell-derived microvesicles are elevated acutely following burns injury, mirroring clinical severity due to the early onset and prevalence of systemic inflammatory response syndrome (SIRS) in these patients. Blood samples were obtained from patients with moderate to severe thermal injury burns, with severe sepsis, and from healthy volunteers. Circulating microvesicles derived from total leukocytes, granulocytes, monocytes, and endothelial cells were quantified in plasma by flow cytometry. All circulating microvesicle subpopulations were elevated in burns patients on day of admission (day 0) compared to healthy volunteers (leukocyte-microvesicles: 3.5-fold, p = 0.005; granulocyte-microvesicles: 12.8-fold, p<0.0001; monocyte-microvesicles: 20.4-fold, p<0.0001; endothelial- microvesicles: 9.6-fold, p = 0.01), but decreased significantly by day 2. Microvesicle levels were increased with severe sepsis, but less consistently between patients. Leukocyte- and granulocyte-derived microvesicles on day 0 correlated with clinical assessment scores and were higher in burns ICU non-survivors compared to survivors (leukocyte MVs 4.6 fold, p = 0.002; granulocyte MVs 4.8 fold, p = 0.003). Mortality prediction analysis of area under receiver operating characteristic curve was 0.92 (p = 0.01) for total leukocyte microvesicles and 0.85 (p = 0.04) for granulocyte microvesicles. These findings demonstrate, for the first time, acute increases in circulating microvesicles following burns injury in patients and point to their potential role in propagation of sterile SIRS-related pathophysiology.